PERSEPSI PESERTA DIDIK TENTANG PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MATA PELAJARAN BIOLOGI - Munir, Asmawati; Sabilu, Murni; Nurfadilla (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the perceptions of independent class XI students about the Pancasila Student Profile Strengthening Project (P5) in Biology at SMAN 3 Kendari. P5 is part of the Independent Curriculum which aims to integrate Pancasila values into learning through a project-based approach. One of the projects studied is